(untitled) (Global Media Journal - German Edition, 2022)
Entering different life and work contexts is fundamental to the practice of ethnographic researchers, journalists, and media development practitioners working in a globalized world. Especially the question of how to get access to their field is something they must find answers for. It is precisely this access that could enable them to get to know, understand and deal with other local contexts. Yet, different barriers, such as language, culture, or power imbalances might be challenging. Thus, possible conflicting perspectives of those from foreign contexts and those local on-site need to be reflected. Furthermore, the so-called “western” perspective and approach of doing things appears to dominate the academic and the professional field of media as well. To continue reading, please open the PDF.